Sewage Sludge Amendment Combined with Green Manuring to a Coastal Mudflat Salt-Soil in Eastern China: Effects on Soil Physicochemical Properties and Maize Yield - Yanchao Bai; Wengang Zuo; Yiyun Yan; Chuanhui Gu; Yongxiang Guan; Lijuan Mei; Weijie Xue; Yuhua Shan; Ke Feng (International Journal of Agronomy)
Sewage sludge and green manure have become widely used organic amendments to croplands in many regions of the world. However, the amending effect of the combination of sewage sludge with green manuring in reclaimed coastal mudflat salt-soil has been unclear yet. This paper was one of earlier studies to investigate and evaluate the effects of sewage sludge amendment combined with green manuring on selected soil physicochemical properties of the mudflat soil in a rain-fed agroecosystem. The mudflat salt-soil was amended by one-time input of sewage sludge at the rates of 0, 30, 75, 150, and 300 t ha−1. After green manuring for three consecutive seasons, maize (Zea mays L.) was planted in 2013 and 2014. The results showed that SSA combined with green manuring decreased bulk density, pH, salinity, and exchangeable sodium percentage of the topsoil (0–20 cm soil layer) and increased aggregate stability, cation exchange capacity, and N and P concentration of the topsoil. As a result, the maize yield increased with the increase of SSA rates. Sewage sludge combined with green manuring can be applied in coastal mudflat salt-soil amendment, which provides an innovative way to create arable land resources and safe disposal of sewage sludge.